2017
DOI: 10.5194/acp-17-14025-2017
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray surface-enhanced Raman spectroscopy (ES-SERS) for probing surface chemical compositions of atmospherically relevant particles

Abstract: Abstract. We present electrospray surface-enhanced Raman spectroscopy (ES-SERS) as a new approach to measuring the surface chemical compositions of atmospherically relevant particles. The surface-sensitive SERS is realized by electrospraying Ag nanoparticle aerosols over analyte particles. Spectral features at v(SO Enhanced spectra of the solid AS and AS / SA particles revealed the formation of surface-adsorbed water on their surfaces at 60 % relative humidity. These observations of surface aqueous sulfate and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 59 publications
2
30
0
Order By: Relevance
“…For example, Ghorai and Tivanski (2010) developed a STXM-based method to study hygroscopic growth of individual submicrometer particles and proposed a method to quantify the mass of water associated with individual particles at a given RH. DRH and ERH values of NaCl, NaBr, and NaNO 3 , determined using STXM (Ghorai and Tivanski, 2010), agreed very well with previous results, and mass hygroscopic growth factors were also reported for these particles. In a following study (Ghorai et al, 2011), STXM was used to investigate hygroscopic growth of individual malonic acid; in addition to measured mass hygroscopic growth factors, near-edge X-ray absorption fine structure spectroscopy (NEXAFS) acquired using STXM suggested that keto-enol tautomerism occurred for deliquesced malonic acid particles (Ghorai et al, 2011).…”
Section: X-ray Microscopysupporting
confidence: 88%
“…For example, Ghorai and Tivanski (2010) developed a STXM-based method to study hygroscopic growth of individual submicrometer particles and proposed a method to quantify the mass of water associated with individual particles at a given RH. DRH and ERH values of NaCl, NaBr, and NaNO 3 , determined using STXM (Ghorai and Tivanski, 2010), agreed very well with previous results, and mass hygroscopic growth factors were also reported for these particles. In a following study (Ghorai et al, 2011), STXM was used to investigate hygroscopic growth of individual malonic acid; in addition to measured mass hygroscopic growth factors, near-edge X-ray absorption fine structure spectroscopy (NEXAFS) acquired using STXM suggested that keto-enol tautomerism occurred for deliquesced malonic acid particles (Ghorai et al, 2011).…”
Section: X-ray Microscopysupporting
confidence: 88%
“…Infrared spectroscopy is very sensitive to adsorbed water and has been widely used to investigate water adsorption (Tang et al, 2016a), as discussed in Section 3.3.1. In contrast, Raman spectroscopy is not sensitive enough to detect adsorbed water; nevertheless, recent work (Gen and Chan, 2017) showed that electrospray surface enhanced Raman spectroscopy was able to detect surface adsorbed water. One important advantage for infrared and Raman spectroscopy is that simultaneous measurement of chemical composition can be provided; therefore, they have been coupled to other techniques (such as optical microscope, electrodynamic balance, and etc.)…”
Section: Discussionmentioning
confidence: 98%
“…To probe smaller particles and improve the potential for Raman spectroscopic analysis of interparticle and intraparticle variation, applications of surface‐enhanced Raman spectroscopy (SERS) and tip‐enhanced Raman spectroscopy (TERS) to the study of aerosols have recently been developed. A SERS method using particles deposited on nanoparticle‐coated substrates to enhance the Raman signal was introduced by Craig et al (), followed by several variations, such as electrospray SERS (ES‐SERS) and surface‐enhanced resonance Raman spectroscopy (SERRS; Craig et al, ; Gen & Chan, ; Sivaprakasam et al, ). TERS uses an atomic force microscope (AFM) tip with a noble metal (e.g., silver) nanoparticle tip to generate enhanced Raman spectra.…”
Section: Measurement Techniques For Aerosol Mixing Statementioning
confidence: 99%